THE INFLUENCE OF PRINCIPAL LEADERSHIP, INNOVATIVE ORGANIZATIONAL CULTURE, AND TEACHER WORK MOTIVATION ON TEACHER PERFORMANCE - Nurul Nurlillah; Nurtanio Agus Purwanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This inquiry is directed toward evaluating the magnitude of influenceexerted by three key predictors Principal Leadership, InnovativeOrganizational Culture, and Work Motivation upon Teacher Performance atSDN 012 Balikpapan Timur and SDIT Darun Najah. Adopting a quantitative approach, this research utilized a census technique, wherein theentire population of 46 teachers served as a saturated sample. Data acquisition relied on Likert-scale questionnaires, while hypothesisverification was conducted utilizing Multiple Linear Regression analysis. Despite initial normality assessments indicating a non-normal distribution (p < 0.001), the analytical process proceeded as the model successfullysatisfied alternative classical assumption prerequisites, specifically validity, reliability, multicollinearity, and heteroscedasticity. The empirical findingsconfirm that, when examined partially, none of the three independentvariables exert a substantial impact on teacher performance; this iscorroborated by probability values exceeding the 0.05 threshold for eachvariable (X1=0.214; X2=0.149; X3=0.364). Furthermore, the coefficient ofdetermination reveals that only 29.8% of the variability in TeacherPerformance is attributable to the combination of these independentvariables. Consequently, the remaining majority proportion (70.2%) stemsfrom external determinants falling outside the scope of this analyticalframework. It is concluded that within the elementary school context of thisregion, these specific factors do not constitute the primary drivers forenhancing teacher performance.